Association between the Demographic Characteristics of Patients and the Severity of COVID-19 - Fadhil, Hayder (University of Thi-Qar Journal of Science, 2023)
The relationship between obesity and COVID-19 is controversial. In addition, the disease’s relationship to sex and re-infection is not fully understood. This study investigated the demographic characteristics of 120 patients in the age range from 27 to 70 years old, without chronic disease, who were infected with COVID-19 and treated at Al-Hussein Teaching Hospital in Thi-Qar Province/Southern of Iraq. In this study, the male increased non-significantly than female 55.83% 44.17% respectively. The infected females had a higher BMI (29.1 ± 6.07kg/m2) than males (26.7 ± 5.99 kg/m2); 12.5% of the male patients and 0.83% of the female patients were previously infected with COVID-19; and 12.5% of the patients and 7.5% of female patients were previously vaccinated against COVID-19. The study noted a positive relationship between BMI and disease severity in both male and female patients and that males had a higher percentage of severe disease than females. The study identified age and BMI had association with disease severity, that COVID-19 occurred more in males than females, and that 80% of patients were not vaccinated against COVID-19.